Occupational Burnout Among Frontline Health Professionals in a High-Risk Area During the COVID-19 Outbreak: A Structural Equation Model - Li, Dan; Wang, YuanYuan; Yu, Hui; Duan, Zhizhou; Peng, Ke; Wang, Nan; Zhou, Qiang; Hu, Xudong; Fang, Ke; Wilson, Amanda; Ou, Jianjun; Wang, Xiaoping (Frontiers in Psychiatry, 2021)
Background: The outbreak of coronavirus disease 2019 (COVID-19) resulted in a substantial workload and stress for frontline health professionals in high-risk areas. Little research has investigated the mechanism of occupational burnout among the frontline health professionals located in the center of the epidemic in Wuhan, China. Methods: A total of 199 frontline health professionals from Wuhan Jinyintan Hospital completed the cross-sectional survey. Mechanisms of occupational burnout (according to the Maslach Burnout Inventory–General Survey, MBI-GS) among the health professionals in Jinyintan Hospital during the COVID-19 outbreak were examined using a structural equation model (SEM). Results: The levels of the three burnout dimensions (emotional exhaustion, cynicism, and professional efficacy) were high at 34.2, 50.8, and 35.2%, respectively. Frontline health professionals in this stressful period reported significantly greater emotional exhaustion (p < 0.001) and job-related cynicism (p < 0.001), but no significant difference in professional efficacy (p = 0.449), when compared to employees in a large multinational company. The SEM results revealed that both acute stress symptoms and psychosomatic symptoms significantly predicted the emotional exhaustion and occupation cynicism dimensions of burnout. Conclusion: The study reveals the occupational burnout mechanism of frontline health professionals during the COVID-19 peak at the time of the outbreak. This study provides an important contribution to understanding the future psychological interventions necessary for frontline health professionals during an epidemic crisis.